2019
DOI: 10.1080/02602938.2019.1686749
|View full text |Cite
|
Sign up to set email alerts
|

The development of academics’ feedback literacy: experiences of learning from critical feedback via scholarly peer review

Abstract: The emerging literature related to feedback literacy has hitherto focused primarily on students' engagement with feedback, and yet an analysis of academics' feedback literacy is also of interest to those seeking to understand effective strategies to engage with feedback. Data from concept map-mediated interviews and reflections, with a team of six colleagues, surface academics' responses to receiving critical feedback via scholarly peer review. Our findings reveal that feedback can be visceral and affecting, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…2 their articles, novice researchers have the potential to enhance their chances of publication and develop a deeper understanding of the publication and research processes, ultimately aiding their integration into the academic community. These findings provide evidence to support the criticism that spesific feedback processes in scholarly journal publishing may possess inherent flaws (Gravett et al, 2020). Therefore, newly-minted researchers need to recognize that their submissions are not a solitary composition, but instead constitute a portion of a broader genre set, encompassing productive and receptive genres, which collectively help to ensure a paper's eventual acceptance (Han & Hyland, 2015).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…2 their articles, novice researchers have the potential to enhance their chances of publication and develop a deeper understanding of the publication and research processes, ultimately aiding their integration into the academic community. These findings provide evidence to support the criticism that spesific feedback processes in scholarly journal publishing may possess inherent flaws (Gravett et al, 2020). Therefore, newly-minted researchers need to recognize that their submissions are not a solitary composition, but instead constitute a portion of a broader genre set, encompassing productive and receptive genres, which collectively help to ensure a paper's eventual acceptance (Han & Hyland, 2015).…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, newly-minted researchers need to recognize that their submissions are not a solitary composition, but instead constitute a portion of a broader genre set, encompassing productive and receptive genres, which collectively help to ensure a paper's eventual acceptance (Han & Hyland, 2015). With this perspective, novice researchers can engage in a developmental and communicative process with journal reviewers' feedback (Gravett et al, 2020). Further research is required to explore the potential impact of this process on beginner researchers' self-perception as researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating timely and thorough feedback [90], professional development opportunities [91], collaborative work settings [91], and integrating feedback [92], on the other hand, can improve assessment preparation and increase student engagement and motivation. Assessment validity and reliability may be increased further by connecting learning objectives with assessment activities [93], employing exam wrappers [94], and introducing formative assessments that are matched with learning outcomes [95]. Furthermore, proctoring with formative feedback can boost student engagement and motivation while also increasing exam validity and reliability [96].…”
Section: Preparing the Assessment Tasksmentioning
confidence: 99%
“…Relating to peer‐review, academics' feedback literacy is much less discussed in the literature. In a recent publication, Gravett et al (2020) reported on a collaborative autoethnography on academics' feedback experiences as authors engaging with critical feedback from journal peer reviewers, arguing that academics are often placed in a situation similar to the one experienced by students in an educational context. While publications on feedback literacy mainly focus on teaching and learning, I would argue that the notion is a very relevant one to journal peer reviewers.…”
Section: What Really Is Feedback?mentioning
confidence: 99%